How to probe the spin contribution to momentum relaxation in topological insulators - Moon-Sun Nam (Nature Portfolio, 2018)
Magnetic scattering may profoundly modify the electronic properties of a topological insulator. Here, Nam et al. report a method enabling separation of the effects of magnetic and non-magnetic scattering by decorating the surface of topological insulators with molecules.